Bruno Touschek 100 Years Memorial Symposium 2021 - Bonolis, Luisa; Maiani, Luciano; Pancheri, Giulia (Springer Proceedings in Physics, 2023)
This open access book celebrates the contribution of Bruno Touschek to theoretical physics and particle colliders in Europe. It contains direct testimonials from his former students, collaborators, and eminent scientists, among them, two Nobel Prize winners in Physics, Giorgio Parisi and Carlo Rubbia. It reviews the main developments in theoretical and accelerator physics in the second half of the twentieth century, while at the same time providing an overview of future prospects worldwide. This book is unique in that it will be of interest to historians of physics and also to the younger generation of researchers. Through the contribution of the leading protagonists, the interested scholar will learn about the past, present status, and relevance of both theoretical and experimental accelerator physics. The overview of Bruno Touschek's life and works across Europe, from pre-war Vienna to Germany, the UK, Italy, and France, adds a human dimension to the scientific narration, while the open access status makes this laudatory book available to anyone with interest.